INTEGRATION OF ISLAMIC VALUES IN SCIENCE LEARNING IN MADRASAH - Firmansyah; Fadlullah; Yesi Purwaningatmaja (Indonesian Journal of Education (INJOE), 2023)
The integration of Islamic values into science learning in the madrasah has a significant impact on students' education and understanding. This integration helps students develop a holistic understanding of the relationship between science and religion, as well as shaping Islamic attitudes and values in the study of science. Moreover, this integration also promotes critical thinking, increases learning motivation, and addresses the potential conflict between Science and Religion. It has a positive impact on science learning in the madrasah, enriching students' understanding of the world and enhancing their moral and spiritual development.